Association of gestational hypertension and preeclampsia with offspring adiposity: A systematic review and meta-analysis - Yan, Shiyu; Lyu, Jinlang; Liu, Zheng; Zhou, Shuang; Ji, Yuelong; Wang, Haijun (Frontiers in Endocrinology, 2022)
Background The association of gestational hypertension (GH) and preeclampsia (PE) with offspring adiposity outcomes had controversial results in different studies. Objective We conducted a systematic review and meta-analysis to evaluate the relationship between maternal GH/PE and offspring adiposity outcomes. Search strategy Studies were identified in PubMed, Embase, and Cochrane databases, with keywords including "gestational hypertension", "preeclampsia", "offspring", "weight", "cohort study", etc., without year restriction. This study was registered with PROSPERO, CRD42022292084. Selection criteria We set the selection criteria for six aspects: population, outcome, time frame, study design, and availability. For the studies included in the meta-analysis, we required the potential confounders in these studies have been adjusted. Data collection and analysis Two reviewers independently evaluated the data from the included studies. The meta-analyses included mean differences, regression coefficients, and corresponding 95% confidence intervals. Results were performed using RevMan software (version 5.4; Cochrane Collaboration). Heterogeneity among the included studies was assessed using the I2 statistic. Main results A total of 16 studies were included in our review, 15 of which were evaluated as high quality. In all offspring, during the early life (28 days-36 months), GH/PE exposure was found to be not or inversely associated with offspring obesity, then become positively associated at larger ages (3-19 years old). In offspring with adverse birth outcomes, the maternal GH/PE-exposed group had a lower weight in the short term (28 days to 18 months), but there was a trend of rapid weight gain as they grew older, compared with the non-exposed group. The meta-analysis showed that the BMI of the female offspring in the maternal PE-exposed group was significantly higher than that of the non-exposed offspring (MD=1.04, 95% CI: 0.67~1.42, P < 0.05). Conclusions The systematic review suggested that maternal exposure to de novo hypertension disorders of pregnancy (HDP) was associated with obesity in offspring, extending from early childhood to adolescence. The meta-analysis showed that PE was associated with higher BMI in female offspring. More studies are needed to conduct stratified analyses by PE/GH, the severity of HDP, or gender.